Seasonal changes in copepod biomass and production in Gamak Bay, Korea - Moon, Seong Yong; Oh, Hyun Ju (Fisheries and aquatic sciences, 2021)
To better understand the ecological functioning of the coastal ecosystem in Gamak Bay on the southern coast of Korea, seasonal changes in the density, biomass, and secondary production of the copepod community were investigated. Environmental measurements (temperature, salinity, and chlorophyll a) and copepod sampling were performed seasonally from January to December 2006. The mean density of copepods (excluding nauplii) varied from 949 to 5,999 ind · m−3; copepod density was at its highest from March to July. The copepod community comprised 32 taxa, including Calanoida, Cyclopoida, and Harpacticoida. The predominant species were Paracalanus parvus s. l., Acartia omorii, Eurytemora pacifica, Oithona similis, A. erythraea, Centropages abdominalis, Pseudodiaptomus marinus, and Calanus sinicus. There were significant spatial and seasonal variations in copepod total biomass, which ranged from 0.33 to 43.10 mg C m−3. Mean secondary production of the copepods in Gamak Bay, estimated as 2.05 ± 1.63 mg C m−3 d−1 using the Huntley and Lopez growth model, was over 2 times higher than the value given by application of the Hirst and Bunker model (1.09 ± 0.85 mg C m−3 d−1). The daily production rate to biomass (P/B) ratio varied between 0.08 and 0.86 d−1 (Huntley and Lopez model), and 0.18 and 0.33 d−1 (Hirst and Bunker model). Our results emphasize the ecological significance of using models to estimate the secondary production of copepods and provides the first report of copepod production in Gamak Bay.